Post-implementation of MFRS 8 “Operating Segment” among listed firms in Malaysia - Johari, Jalila (EDP Sciences, 2017)
This study examined the level of disclosure among Malaysian listed firms with respect to segment reporting under new accounting standard MFRS 8 (IFRS 8). It also aimed to determine how these firms defined the chief operating decision maker (CODM) during the disclosure of segment information. Study results showed that the way firms disclosed segment information tended to vary between companies, since disclosure was dependent on company management purposes and business activities. The results also showed that only a few Malaysian firms supply information about their CODM. In summary, this study provides a fairly up-to-date description of the status of segment disclosure post-implementation of MFRS 8.